Expert Consensus to Guide the Classification of Paralympic Swimmers With Vision Impairment: A Delphi Study - Ravensbergen, Henrike Joanna Cornelie; Genee, Amarens Doutsen; Mann, David Lindsay (Frontiers in Psychology, 2018)
The International Paralympic Committee requires their member sports to develop a classification system that is sport-specific, meaning that the specific ‘class’ in which an athlete competes should be tailored to how their impairment affects performance in that particular sport. However, Paralympic swimmers with vision impairment (VI) currently compete in classes that were developed on the basis of legal definitions of blindness, failing to consider how vision impacts swimming performance. The aim of this study was to reach expert consensus on the specific requirements for a sport-specific system of classification for VI swimming. A three-round Delphi review was conducted with a panel of 16 people with expertise in VI swimming either as an athlete, coach, administrator, or scientist. There was clear consensus among the panel that the current classification system used for VI swimming fails to fulfil the aim of minimising the impact of VI on the outcome of competition. Particularly, the panel agreed that there are a range of aspects of visual function (e.g., depth perception and contrast sensitivity) that are important for optimal swimming performance, yet are not assessed using the current classification system. There was also strong agreement that the age at which VI is acquired will substantially impact the ability of a swimmer to reach their potential in the pool. The panel encourages a change in the way that swimmers with vision impairment are classified for Paralympic competition. Clear guidance has been provided for how to further the development of an evidence-based classification.